A review on co-pyrolysis of agriculture biomass and disposable medical face mask waste for green fuel production: recent advances and thermo-kinetic models - Wee, Melvin X. J.; Chin, Bridgid; Saptoro, Agus; Yiin, Chung L.; Sunarso, Jaka; Chew, Jiuan Jing; Yusup, Suzana; Sharma, Abhishek (2023)
The Association of Southeast Asian Nations is blessed with agricultural resources, and with the growing population, it will continue to prosper, which follows the abundance of agricultural biomass. Lignocellulosic biomass attracted researchers’ interest in extracting bio-oil from these wastes. However, the resulting bio-oil has low heating values and undesirable physical properties. Hence, co-pyrolysis with plastic or polymer wastes is adopted to improve the yield and quality of the bio-oil. Furthermore, with the spread of the novel coronavirus, the surge of single-use plastic waste such as disposable medical face mask, can potentially set back the previous plastic waste reduction measures. Therefore, studies of existing technologies and techniques are referred in exploring the potential of disposable medical face mask waste as a candidate for co-pyrolysis with biomass. Process parameters, utilisation of catalysts and technologies are key factors in improving and optimising the process to achieve commercial standard of liquid fuel. Catalytic co-pyrolysis involves a series of complex mechanisms, which cannot be explained using simple iso-conversional models. Hence, advanced conversional models are introduced, followed by the evolutionary models and predictive models, which can solve the non-linear catalytic co-pyrolysis reaction kinetics. The outlook and challenges for the topic are discussed in detail.